Semantic Features Of The Words “Hot”, “Warm”, “Cool”, “Cold” In English And “Nóng”, “Ấm”, “Mát”, “Lạnh” In Vietnamese From Functional Grammar Perspective - Bùi Ý Lan (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis is designed to investigate some semantic features of the words “Hot”, “Warm”, “Cool”, “Cold” in English and “Nóng”, “Ấm”, “Mát”, “Lạnh” in Vietnamese. Particularly, we consider and analyze how the words are embodied in a Clause as Representation. For observation and analysis, over 800 samples involve novels, short stories and websites in English and in Vietnamese, which are written by native writers, not translational versions and are available online. Using qualitative and quantitative research approaches, the data are grouped into categories depending on their semantic features of these words when they are presented in processes in the Clause as Representation. Then a contrastive analysis is done based on the outlook of functional grammar to point out the similarities and differences in using the words between the two languages. In a broader sense, the main goal of this research is to study the semantic features of the words “Hot”, “Warm”, ‘Cool”, “Cold” in English and “Nóng”, “Ấm”, “Mát”, “Lạnh” in Vietnamese from functional grammar perspective in order to provide those engaged in English teaching and learning in Vietnam a number of implications in using these words effectively.